PENGARUH KARAKTERISITK PERUSAHAAN, AUDIT QUALITY, DAN MANAGERIAL OWNERSHIP TERHADAP MANAJEMEN LABA - Aldani, Malika Putri; Indrastuti, Dewi Kurnia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to obtain empirical evidence regarding the effect of firm characteristics in the form of firm age, leverage profitability, firm size, sales growth, managerial ownership, and audit quality as independent variables on earnings management as dependent variable. The population of this research are cyclicals and non-cyclicals sector companies listed in Indonesia Stock Exchange during 2020 until 2021. The sample selection method used is purposive sampling method, with the result that 67 companies or 201 data point meet the criteria. This research is using multiple regression as the data analysis methos and hypothesis testing. The empirical evidence on this research shows that profitability has a positive effect on earnings management. Profitability has a positive relationship with earnings management means the more profitable a company is, the more earnings management practices it will employ to maintain its deemed superior performance through increased profits. Earnings management is negatively impacted by growth in sales. Strong sales growth is a positive indicator and facilitates investor attraction, which leads to a decrease in earnings management strategies by businesses. On the other hand, managerial ownership, audit quality, firm age, leverage, and firm size have no effect on earnings management.